2005
DOI: 10.1093/hmg/ddi424
|View full text |Cite
|
Sign up to set email alerts
|

Telomere instability in the male germline

Abstract: Telomeres play a key role in upholding the integrity of the genome, and telomerase expression in spermatogonial stem cells is responsible for the maintenance of telomere length in the human male germline. We have previously described extensive allelic variation in somatic cell telomere length that is set in the zygote, the ultimate source of which may be the germline. This implies that despite telomerase activity, substantial telomere length variation can be generated and tolerated in the germline; in order to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

11
107
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(121 citation statements)
references
References 53 publications
11
107
3
Order By: Relevance
“…The key might be age-dependent telomere dynamics in sperm. Mean telomere length in sperm does not decrease, and, in fact, increases with the donor's age [34,35], a phenomenon we confirmed. The donor's age effect on sperm telomere length was not due to the change in the sperm profile of MMP, a parameter serving as an indicator of sperm motility and 'fertilizing' capacity [36].…”
Section: Discussionsupporting
confidence: 74%
“…The key might be age-dependent telomere dynamics in sperm. Mean telomere length in sperm does not decrease, and, in fact, increases with the donor's age [34,35], a phenomenon we confirmed. The donor's age effect on sperm telomere length was not due to the change in the sperm profile of MMP, a parameter serving as an indicator of sperm motility and 'fertilizing' capacity [36].…”
Section: Discussionsupporting
confidence: 74%
“…caused by increases in sperm TL as a man ages. Although longer sperm TL in older men compared with younger men (4,14,15) provides convergent evidence for this prominent hypothesis, it is also known that sperm donors represent nonrandom samples of the population (35,36). It is possible that older men who volunteer to donate sperm have better reproductive health and longer sperm TL and that a similar selection bias results in men with longer sperm TL tending to reproduce at later ages.…”
Section: Discussionmentioning
confidence: 92%
“…The longer TL among offspring of older fathers has been explained by the fact that sperm TL are longer in older men (4,14,15), with high telomerase activity in testes being the most common explanation for the increase in sperm TL seen with age (16,31). Because men produce an estimated 100 million sperm cells daily (32)(33)(34), telomere maintenance mechanisms are required to avoid rapid telomere shortening (17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast Baird et al (2005;Hewakapuge et al, 2008;Karlsson et al, 2008) confirmed that age estimation based on telomere shortening measured with real-time PCR is not appropriate for age estimation in forensic practice, as there was a relatively large variation between individuals, e.g., in the study of Karlsson et al (2008), R 2 = 0.3 with standard error of age prediction estimated to be much higher as ±22 years, while in the study of Hewakapuge et al (2008), R 2 value was 0.037 which was significantly low.…”
Section: Discussionmentioning
confidence: 88%